Current Status Of Educational Research Linked To Teacher Practice In Peru - et. al, Mariana Silva Balarezo , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To achieve quality education worldwide, it is necessary for teachers to investigate in their educational context in order to understand and intervene in teaching-learning process. The present article aims to explain the current state of educational research linked to teaching practice. The study was carried out between January to April 2021, in department of La Libertad, its capital Trujillo being located in northern Peru. The applied methodology responds to the qualitative approach and cross-sectional phenomenological research design. Participants were 46 teachers from initial, primary and secondary educational levels of public schools. Information was collected through a semi-structured interview and analysis of information was processed through Atlas software. ti7 that allowed to organize and hierarchize the data in categories and codes, starting with four a priori categories and in the process three new categories emerged. Results have found a serious contradiction between positive conception of teaching staff about educational research as a contribution to education and the link between it in their teaching practice. Conclusions clarify the panorama of the teaching conception about research and the reasons why they have not been able to link it to their teaching practice.